Striatal Control of Movement: A Role for New Neuronal (Sub-) Populations? - Fieblinger, Tim (Frontiers in Human Neuroscience, 2021)
The striatum is a very heterogenous brain area, composed of different domains and compartments, albeit lacking visible anatomical demarcations. Two populations of striatal spiny projection neurons (SPNs) build the so-called direct and indirect pathway of the basal ganglia, whose coordinated activity is essential to control locomotion. Dysfunction of striatal SPNs is part of many movement disorders, such as Parkinson’s disease and L-DOPA-induced dyskinesia. In this mini review, I will highlight recent studies utilizing single-cell RNA sequencing to investigate the transcriptional profiles of striatal neurons. These studies discover that SPNs carry a transcriptional signature, indicating both their anatomical location and compartmental identity. Furthermore, the transcriptional profiles reveal the existence of additional distinct neuronal populations and previously unknown SPN sub populations. In a parallel development, studies in rodent models of Parkinson’s disease and L DOPA induced dyskinesia report that direct pathway SPNs do not react uniformly to L DOPA therapy, and that only a subset of these neurons is underlying the development of abnormal movements. Together, these studies demonstrate a new level of cellular complexity for striatal (dys-) function and locomotor control.